2010
DOI: 10.1002/pbc.22931
|View full text |Cite
|
Sign up to set email alerts
|

Quality of health in survivors of childhood acute myeloid leukemia treated with chemotherapy only: A NOPHO‐AML study

Abstract: The self-reported health of children treated on NOPHO-AML protocols without HSCT was good, and their use of health care services was limited. Reported health and social outcomes were comparable to those of their siblings. Many survivors were smoking which may increase the risk of late effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
(43 reference statements)
3
52
0
Order By: Relevance
“…Second malignant neoplasms are rare in pediatric AML with a 15-year cumulated incidence of less than 2%. 23,24 GO is not known to be associated with secondary malignancies and our observation may be a chance finding.…”
Section: Remission Achievedmentioning
confidence: 80%
“…Second malignant neoplasms are rare in pediatric AML with a 15-year cumulated incidence of less than 2%. 23,24 GO is not known to be associated with secondary malignancies and our observation may be a chance finding.…”
Section: Remission Achievedmentioning
confidence: 80%
“…A report from the Childhood Cancer Survivor Study found that adult childhood cancer survivors were employed in lower-skilled jobs than their siblings [21]. A study including survivors of childhood myeloblastic AL treated by chemotherapy only reported that the number of full-time employees was significantly lower among the survivors than among their siblings [23]. However, the authors noted a higher proportion of students among the survivors.…”
Section: Discussionmentioning
confidence: 96%
“…are clearly differentiated. Many previous studies that have explored the employment status of childhood cancer survivors have reported their results concerning unemployed survivors without differentiating, for example, students or those not working by choice [6,17,20,22,23,31,32]. In our study, active childhood AL survivors (currently on the labor market) were compared to the active general French population to explore the potential difficulties in accessing employment for the survivors who were likely to work.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Introduction of targeted treatment modalities could allow a better stratification of patients, and use of more individualized therapies may lead to further improvements of treatment outcomes. The new treatment protocols for children with AML are expected to improve the treatment results and decrease the late side effect rates [13, 14, 29, 30]. However, further progress in AML therapy seems possible because of continued cooperation of oncology centers within large international study groups.…”
Section: Discussionmentioning
confidence: 99%